The Influence of Destination Image and Positioning Strategy Against the Decision to Visit Tourists to Pagang Island Tourist Attraction in Sungai Pisang Village, Padang City - Syahputra, Chandra; Nasrul, Firhan Pratama (Adpebi Science Series, 2024)
This study aims to find out how the Destination Image variable and Positioning Strategy affect the decision to visit the Pagang Island Tourist Attraction in Sungai Pisang Village, Padang City. The type of data used in this study is quantitative in the form of questionnaires from visitors to the Pagang Island Tourist Object in Sungai Pisang Village, Padang City. The population used in this study is all Visitors to the Pagang Island Tourist Attraction in Sungai Pisang Village, Padang City. With a sample of 100 visitors. The results of the t-test showed that Destination Image and Positioning Strategy had a positive and significant effect on the decision to visit the Pagang Island Tourist Object in Sungai Pisang Village, Padang City The results of the F-Test showed that the variables of Destination Image and Strateggi Positiioning together had a positive effect on the decision to visit the Pagang Island Tourist Object in Sungai Pisang Village, Padang City. From the results of the determinant coefficient analysis, the R Adjusted Square (R2) value was obtained of 0.340, which means that 34% of the variables of the decision to visit can be explained by the variables Destination Image and Strateggi Positiioning, while the rest (66%) can be explained by other variables that are not studied in this study.